2022
DOI: 10.3390/w14233960
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Irrigation Scheduling for Improved Irrigation Water Management in Bilate Watershed, Rift Valley, Ethiopia

Abstract: The availability of water for agricultural production is under threat from climate change and rising demands from various sectors. In this paper, a simulation-optimization model for optimizing the irrigation schedule in the Bilate watershed was developed, to save irrigation water and maximize the yield of deficit irrigation. The model integrated the Soil and Water Assessment Tool (SWAT) and an irrigation-scheduling optimization model. The SWAT model was used to simulate crop yield and evapotranspiration. The J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Farmers' practices have lower yields and water productivity. This is the same as reported by [35] IV.CONCLUSIONS…”
Section: Water Productivitysupporting
confidence: 90%
“…Farmers' practices have lower yields and water productivity. This is the same as reported by [35] IV.CONCLUSIONS…”
Section: Water Productivitysupporting
confidence: 90%
“…Further, optimization of irrigation levels is a key factor in maximizing crop yield and water use efficiency. Wabela et al (2022) [3] found that optimizing irrigation based on moisture-stress-sensitivity levels can save irrigation water and maximize crop yield. The integration of IoT and automation in irrigation systems has the potential to transform farming practices, promoting sustainable agriculture and increasing efficiency (Archana et al, 2023; Kantilal et al, 2023 and Kaushik, 2023) [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Globally, agriculture is a significant consumer of freshwater resources, and the projected acceleration in global population growth highlights the imminent surge in food demand, which directly impacts agricultural water usage [1,2]. Moreover, escalating carbon dioxide emissions contribute to an upsurge in greenhouse gases and accelerate climate change.…”
Section: Introductionmentioning
confidence: 99%